RADIATION FROM 3D SOURCES IN THE PRESCENCE OF 2D COMPOSITE OBJECTS OF ARBITRARY CROSS-SECTIONAL SHAPE - Kishk, Ahmed A. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A method of moment code for computing the radiation from arbitrarily oriented narrow slots or straight dipoles in the vicinity of a two dimensional (2D) multi-region composite cylinder of arbitrary cross-sectional shape and infinite extension in the z-direction is developed. The dipoles and the slots are represented by known equivalent electric and magnetic currents distributions, respectively. The finite extent of the sources are included by Fourier transforming the equivalent electric and magnetic source currents along the infinite cylinder axis. The computed radiatiation patterns are compared to results computed by other methods and measurements. Radiation patterns are predicted both in the elevation and azimuthal planes.